2012
DOI: 10.1159/000335431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Endoscopic and Histological Differentiations between Crohn’s Disease and Intestinal Tuberculosis

Abstract: Background and Aim: Differentiating Crohn’s disease from intestinal tuberculosis often challenges clinicians in countries where tuberculosis and Crohn’s disease coexist. The aim of this study was to screen out clinical, endoscopic and histological features which may be helpful in distinguishing Crohn’s disease from intestinal tuberculosis. Methods: 43 patients with a confirmed diagnosis of intestinal tuberculosis and 53 patients with Crohn’s disease were recruited for this study. Their clinical, endoscopic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 29 publications
0
59
0
2
Order By: Relevance
“…There are many proposed clinical, radiological, endoscopic, and histological features that distinguish ITB from CD, including a prolonged illness, diarrhea, hematochezia, weight loss, extraintestinal manifestations, fever, ascites, deep linear ulcers, cobble-stone appearance, involvement of the sigmoid colon, coexisting pulmonary lesions, and abdominal lymphadenopathy, etc. (20-22). In the present study, perianal disease and longitudinal ulcers were more common in the CD patients, whereas night sweats, ascites, and circumferential ulcers were more common in the ITB patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are many proposed clinical, radiological, endoscopic, and histological features that distinguish ITB from CD, including a prolonged illness, diarrhea, hematochezia, weight loss, extraintestinal manifestations, fever, ascites, deep linear ulcers, cobble-stone appearance, involvement of the sigmoid colon, coexisting pulmonary lesions, and abdominal lymphadenopathy, etc. (20-22). In the present study, perianal disease and longitudinal ulcers were more common in the CD patients, whereas night sweats, ascites, and circumferential ulcers were more common in the ITB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal tuberculosis (TBC) and colopathy induced by non-steroidal anti-inflammatory drug (NSAID) can mimic Crohn's disease (CD) and thus can cause diagnostic difficulties (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that CD and TBC overlap in clinical, endoscopic and histological features (2)(3)(4). Sacroiliitis (SI) is one of the most frequent extraintestinal manifestations in patients with inflammatory bowel disease (IBD) and can complicate medical behavior (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations